Physical growth and non-verbal intelligence: Associations in Zambia - Hein, Sascha (J Pediatr, 2014)
OBJECTIVES: To investigate normative developmental BMI trajectories and associations of physical growth indicators (ie, height, weight, head circumference [HC], body mass index [BMI]) with non-verbal intelligence in an understudied population of children from Sub-Saharan Africa. STUDY DESIGN: A sample of 3981 students (50.8% male), grades 3 to 7, with a mean age of 12.75 years was recruited from 34 rural Zambian schools. Children with low scores on vision and hearing screenings were excluded. Height, weight and HC were measured, and non-verbal intelligence was assessed using UNIT-symbolic memory and KABC-II-triangles. RESULTS: Results showed that students in higher grades have a higher BMI over and above the effect of age. Girls showed a marginally higher BMI, although that for both boys and girls was approximately 1 SD below the international CDC and WHO norms. Controlling for the effect of age, non-verbal intelligence showed small but significant positive relationships with HC (r = .17) and BMI (r = .11). HC and BMI accounted for 1.9% of the variance in non-verbal intelligence, over and above the contribution of grade and sex. CONCLUSIONS: BMI-for-age growth curves of Zambian children follow observed worldwide developmental trajectories. The positive relationships between BMI and intelligence underscore the importance of providing adequate nutritional and physical growth opportunities for children worldwide and in sub-Saharan Africa in particular. Directions for future studies are discussed with regard to maximizing the cognitive potential of all rural African children.